Simvastatin protects bladder and renal functions following spinal cord injury in rats - Shunmugavel, Anandakumar (BioMed Central, 2010)
BACKGROUND: Urinary bladder and renal dysfunction are secondary events associated with spinal cord injury (SCI) in humans. These secondary events not only compromise quality of life but also delay overall recovery from SCI pathophysiology. Furthermore, in experimental models the effects of SCI therapy on bladder and renal functions are generally not evaluated. In this study, we tested whether simvastatin improves bladder and renal functions in a rat model of experimental SCI. METHODS: SCI was induced by controlled contusion of T9-T10 in adult female rats. Simvastatin (5 mg/Kg body weight) was administered at two hours after SCI and repeated every 24 hours until the end point. Simvastatin-treated SCI animals (simvastatin group) were compared with vehicle-treated SCI animals (vehicle group) in terms of the Basso Beattie Bresnahan score, tissue morphology, cell death, and bladder/renal functions. RESULTS: The urinary bladder of vehicle animals showed a 4.3-fold increase in size and a 9-fold increase in wet weight compared to sham animals. Following SCI, the urine to plasma osmolality ratio increased initially but decreased 1 week after SCI. Hematoxylin and eosin staining of bladder tissue showed transitional epithelial hyperplasia, degeneration of lamina propria, and enlargement of tunica adventia in addition to detrusor muscle hypertrophy. Rats treated with simvastatin for 14 days displayed remarkable recovery by showing decreased bladder size and maintenance of a normal urine/plasma osmolality ratio, in addition to improved locomotion. The muscularis layer of the bladder also regained its compact nature in simvastatin animals. Moreover, SCI-induced renal caspase-3 activity was significantly decreased in the simvastatin group indicating the ability of simvastatin to reduce the renal tubular apoptosis. CONCLUSION: Post-injury administration of simvastatin ameliorates bladder and renal dysfunction associated with SCI in rats.